Fine-tuning protein language models unlocks the potential of underrepresented viral proteomes - Sawhney,Rajan; Ferrell,Barbra D.; Dejean,Thibaut; Schreiber,Zachary; Harrigan,William; Polson,Shawn W.; Wommack,K. Eric; Belcaid,Mahdi (PeerJ, 2025)
Protein language models (pLMs) have revolutionized computational biology by generating rich protein vector representations, or embeddings—enabling major advancements in de novo protein design, structure prediction, variant effect analysis, and evolutionary studies. Despite these breakthroughs, current pLMs often exhibit biases against proteins from underrepresented species, with viral proteins being particularly affected, frequently referred to as the “dark matter” of the biological world due to their vast diversity and ubiquity, yet sparse representation in training datasets. Here, we show that fine-tuning pre-trained pLMs on viral protein sequences, using diverse learning frameworks and parameter-efficient strategies, significantly enhances representation quality and improves performance on downstream tasks. To support further research, we provide source code for fine-tuning pLMs and benchmarking embedding quality. By enabling more accurate modeling of viral proteins, our approach advances tools for understanding viral biology, combating emerging infectious diseases, and driving biotechnological innovation.
Keywords: Proteomics; Protein Language Models; Artificial Intelligence; Viruses